Decision-based median filter using local signal statistics - Florencio, Dinei; Schafer, Ronald (Proceedings SPIE 2308, Visual Communications and Image Processing '94, 1994)
Noise removal is important in many applications. When the noise has impulsive characteristics, linear techniques do not perform well, and median filter or its derivatives are often used. Although median-based filters preserve edges reasonably well, they tend to remove some of the finer details in the image. Switching schemes–where the filter is switched between two or more filters–have been proposed, but they usually lack a decision rule efficient enough to yield good results on different regions of the image. In this paper we present a strategy to overcome this problem. A decision rule based on the second order local statistics of the signal (within a window) is used to switch between the identity filter and a median filter. The results on a test image show an improvement of around 4 dB over the median filter alone, and 2 dB over other techniques.